Criteria for Assessing the Basic Competences of the Modern Teacher - Abdulahatova Shohsanam Adhamjon qizi (Scientific Trends, 2024)
In the article, the author discusses the essence of the basic competencies of modern students. He also demonstrated how to assess basic competencies from a historical perspective and analyzed the process empirically.
Keywords: Learning process, critical thinking, basic competence, logic, innovative technologies, assessment, historical event, criteria, competencies, analysis and synthesis, analysis, feedback, method, qualification, teacher, analysis.